Penerapan Metode Simple Additive Weighting Dalam Pemberian Dana Bantuan Pemerintah Kota Pada Lingkungan XI Daerah Kwala Bekala - Tesa Aurelia Siregar; Nola Dita Puspa; Dwika Assrani (Forum Kerjasama Pendidikan Tinggi, 2021)
City government assistance given by the government to the wrong people often occurs, the aid distributor only gives to the closest relatives, not people who really need it, social inequality occurs. The uneven distribution of basic needs is due to the government's inaccuracy in collecting data on underprivileged citizens and residents who have been laid off and closing access to trade when the Covid-19 pandemic has made the community's economy slump drastically. From this problem, a decision support system is needed to help aid distributors select people who are entitled to be given assistance with the Simple Additive Weighting (SAW) method approach and the results of this decision will be obtained from 1-15 candidates who really deserve to get city government assistance and reduce fraud in providing assistance during the Covid-19 Pandemic.